The Effect of Some Essential Oils on the Growth of Bacteria Paenibacillus (Bacillus) larvae Causing American Foulbrood Disease to Honey Bees (Apis mellifera L.) - Mahmud, Ahmad Motaz Billah; Abu Ghorra , Mahmud; Alburaki , Ali Khaled (Latakia University Journal -Biological Sciences Series, 2013)
The effect of some essential oils taken from Cinnamomum zeylanicum, Citrus limonum and Rosmarinus Officinalis was investigated in relation to the growth of bacteria Paenibacillus larvae which causes American Foulbrood disease that affects world honey bees Apis mellifera L. The study was carried out in the laboratories of the Faculty of Agriculture, Damascus University from 2012 till 2013. This is in order to contribute to preparing an integrated pest management program for American Foulbrood disease. The oils were extracted from the plants using steam distillation. The effects of the concentrations of oils on the growth of P. larvae were tested between (3.90625 - 500 µg/ml) using agar disc diffusion in petri plates. Results showed that the essential oils used stop the growth of P. larvae in some of their concentrations. The minimal inhibitory concentrations which stop the growth of P. larvae of the oils of Cinnamomum zeylanicum, Citrus limonum and Rosmarinus officinalis were recorded at 31.25 µg/ml, 62.5 µg/ml, 125 µg/ml respectively.